Bullying Prevalence among Adolescents: Potential Social Stressor to Young Minds - Jilani, Uzma Aamir; Wahab, Farah; Gilani, Mahnur (Technium Social Sciences Journal, 2020)
Bullying among youth is like an epidemic all around the world. It has critical and damaging effects on the mental health of the affected. Bullying can lead to psychosocial morbidity and adjustment problems in the bully, victims, and those who witness. A study was conducted to investigate the prevalence of this social issue among adolescents in the largest city of Pakistan. The purpose of this survey was to evaluate the extent of bullying prevalence, to determine frequencies of different types of bullying across genders, to raise awareness of the bullying phenomenon among adolescents, and to identify the coping strategies used to stop bullying. In the survey, 241 children aged 12 to 15, participated through convenient sampling, and completed a directly administered questionnaire. The result of this survey suggests that bullying is pervasive among adolescents in Pakistan and thus a significant proportion of the community is at risk of developing psychosocial ailments. There is a need for a well-rounded global effort to design a strategy against bullying that can be implemented by schools, parents, teachers, and students.